Quand la lettre s'efface devant le téléphone... Le français parlé dans des romans téléphoniques: Fil à fil de Marguerite Cassan et Mardi à l'aube de Lucie Faure - Kaló, Krisztina (Verbum – Analecta Neolatina, 2005)
For centuries the letter was considered to be the best way of communication when meeting was impossible between people far away from each other. At modern times we also have the telephone to bring our family or friends closer. A telephone conversation is more personal, more vivid and takes less time. 18th century French literature produced fictive letters to create fascinating novels. Two contemporary authors, Marguerite Cassan and Lucie Faure, attempted to do the same with fictive phone-calls in their novels: Fil à fil ('Line to line') and Mardi à l'aube ('Tuesday at dawn'), respectively. An evident outcome of the "live" conversations is that the language of the novels is strikingly close to spoken French. The present paper wishes to detect the modus operandi of creating the illusion of spoken language in writing.